Rare Presentations of Takayasu Arteritis: A Case Series - Mondal, Sudipta; Shanmugam, Sedhupathi; Kumar, Swasthi S.; Namboodiri, Narayanan; Radhakrishnan, Jayakrishnan; Pitchai, Shivanesan (Indian Journal of Radiology and Imaging, 2024)
Takayasu arteritis (TA) is a form of large vessel vasculitis that may lead to fibrosis, stenosis, or aneurysm formation of vessels. Its presentation varies depending on the arterial beds involved. We report 3 cases out of around 150 cases of TA with rare initial presentations of brachial plexopathy caused by an axillary artery aneurysm, complicated type A intramural hematoma, and renal artery aneurysms along with abdominothoracic TA presenting as a pulsatile abdominal mass.
Keywords: Takayasu arteritis; axillary artery aneurysm; brachial plexopathy; intramural hematoma; dissection; abdominal artery; renal artery; case series